L’inscription latino-palmyrénienne de South Shields - Lipiński, Edward (Anabasis. Studia Classica et Orientalia, 2019)
A bilingual inscription in Latin and in Palmyrene is engraved on a stele representing a sitting lady and found at South Shields (England). This is a funerary relief offered by the lady’s husband in memory of his wife, dead at the age of thirty. She belonged to the Catavellavnian Celtic tribe of central England and is said to be a freedwoman. Her husband was Pamyrene and most likely belonged to a Syrian cohort of the Roman army, serving at Hadrian’s Wall around 200 A.D., as indicated by the man’s Latin epitaph, found some 40 km west of South Shields. The man died at the age of sixty-eight and was then a vexillarius, i.e. a veteran still serving as a reserve soldier. The inscriptions witness to multi-cultural relations with a conscious preservation of distinct national identities.